2018
DOI: 10.1177/0300060518755148
|View full text |Cite
|
Sign up to set email alerts
|

Early or late cranioplasty following decompressive craniotomy for traumatic brain injury: A systematic review and meta-analysis

Abstract: ObjectiveTo evaluate the effectiveness of early (<3 months) cranioplasty (CP) and late CP (>3 months) on post-operative complications in patients receiving decompressive craniotomy (DC) for traumatic brain injury (TBI).MethodsThe Cochrane Library, PubMed and EMBASE databases were systematically searched for studies published prior to May 21, 2017. A meta-analysis examined post-operative overall complication rates, infection rates, subdural fluid collection and operating times according to early and late CP.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…While waiting for results of an ongoing randomized controlled trial (RCT) on early vs. late CP promoted by NIHR Global Health Research Group on Neurotrauma, the timing of reconstructive CP should rather be based on an objective case-by-case assessment of the neurological status of each patient, resolution of brain swelling, and complications associated with large calvarial defects rather than arbitrary time windows (73) and should be performed as soon as brain swelling resolves on CT scan, provided that the patient is not in an infectious state (89).…”
Section: Discussionmentioning
confidence: 99%
“…While waiting for results of an ongoing randomized controlled trial (RCT) on early vs. late CP promoted by NIHR Global Health Research Group on Neurotrauma, the timing of reconstructive CP should rather be based on an objective case-by-case assessment of the neurological status of each patient, resolution of brain swelling, and complications associated with large calvarial defects rather than arbitrary time windows (73) and should be performed as soon as brain swelling resolves on CT scan, provided that the patient is not in an infectious state (89).…”
Section: Discussionmentioning
confidence: 99%
“…Incision complications may be frequent with early CP among patients with severe TBI having Glasgow Coma Scale scores of 3-8 points and bilateral frontotemporal bone window collapse after DC, whereas the long-term prognosis (according to the Glasgow Outcome Scale scores) may not differ between early and late CP (22). A meta-analysis found that early surgery can reduce the operation time and subdural effusion, and may be related to fewer scars (23). Delayed CP and the development of hydrocephalus are associated with poor prognosis in patients with severe TBI (17,24).…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…Our results add valuable information to solve the current equipoise regarding the management and timing of cranioplasty in the presence of a hydrocephalus requiring shunt treatment [ 10 , 14 , 15 ]. While there seems to be a consensus among most studies that a VPS is a major risk factor for complications in cranioplasty procedures including subdural or epidural fluid collections, intracerebral hemorrhage, infections, bone flap resorption, and seizures, the timing of these two procedures, i.e., as a one-stage or two-stage procedures, is less clear.…”
Section: Discussionmentioning
confidence: 99%